Retrospective Observational Study on the Characteristics of Pain and Associated Factors of Breakthrough Pain in Advanced Cancer Patients - Rongrong Fan; Xuying Li; Siyu Yang; Xiaofan Bu; Yongyi Chen; Ying Wang; Cuiling Qiu (Pain Research and Management)
Objective. This study aimed to conduct a retrospective observational study to understand the status of characteristics of pain and identify potential variables influencing the clinical presentation of breakthrough cancer pain (BTP) in advanced cancer patients. Methods. Advanced cancer patients over 18 years of age; diagnosed with cancer of any type and stage III or IV in the palliative care ward with available data were enrolled between 2018 and 2020. Demographic data and pain-related information were collected by using structured electronic extraction form from Hospital Information System (HIS). Patients who had well-controlled background pain with an intensity ≤4 on a 0–10 numerical scale for >12 hours/day, the presence of transient exacerbations of pain with moderate-severe intensity (≧5), and clearly distinguish from background pain were regarded to have suffered BTP. Spearman correlation was conducted to explore the relationship between pain score and demographics characteristics. Factors significant in univariate analysis were included in the multiple regression model to explore independent predictive factors associated with the BTP. Results. Of 798 advanced cancer patients, the mean age was 56.7 (SD = 11.84) years. Lung cancer (29.95%) was the most common cancer, and pain (93%) was the most common symptom. More than half (n = 428, 53.6%) of the patients experienced BTP. The median number of BTP episodes was 4 (IQR = 2, 7, range: 1–42). The median intensity of BTP was 6 (IQR = 6, 7, range 5–10). Patients with severe background pain or BTP had longer hospital stay and more symptoms. Besides, more severe background pain was related to higher activity of daily living. Intramuscular injection of hydromorphone hydrochloride was the main medication for BTP onset. Younger age, background pain, anorexia, and constipation were independently associated with the presentation of BTP. BTP pain intensity was independently associated with bloating. Symptom numbers were an independent factor and positively associated with BTP episodes. Conclusions. BTP resulted in poor prognosis, which has a variable presentation depending on interdependent relationships among different characteristics. Good controlling of background pain and assessment of pain-related symptoms are essential for BTP management. BTP should be managed individually, especially the invisible pain among aged patients. Furthermore, BTP-related education and training were still needed.